Investigation of Citrus aurantiifolia Leaves Extract as Corrosion Inhibitor for Mild Steel in 1 M HCL - R. Saratha; S. V. Priya; P. Thilagavathy (E-Journal of Chemistry)
The inhibition efficiency of acid extract of leaves of Citrus aurantiifolia [CAL] plant on the corrosion of mild steel in 1 M HCl was investigated by weight loss measurements and electrochemical studies. The corrosion rate of mild steel and the inhibition efficiencies of the extract were calculated. The results obtained show that the extract could serve as an effective inhibitor for the corrosion of mild steel in HCl media. Inhibition was found to increase with increasing concentration of the plant extract. The inhibitive action of plant extract is discussed on the basis of adsorption of stable complex at the mild steel surface. Theoretical fitting of different isotherms, Langmuir, Temkin, Freundlich, Frumkin, Flory-Huggins and the kinetic thermodynamic model, were tested to clarify the nature of adsorption. Polarisation curves revealed that this inhibitor act as a mixed type inhibitor and the inhibition efficiency of up to 97.91% can be obtained. The surface analysis study confirms the corrosion of mild steel and its inhibition by the inhibitor CAL.